The Evolution of Sensory Placodes - Francoise Mazet (The Scientific World Journal)
The vertebrate cranial sensory placodes are ectodermal embryonic patches that give rise to sensory receptor cells of the peripheral paired sense organs and to neurons in the cranial sensory ganglia. Their differentiation and the genetic pathways that underlay their development are now well understood. Their evolutionary history, however, has remained obscure. Recent molecular work, performed on close relatives of the vertebrates, demonstrated that some sensory placodes (namely the adenohypophysis, the olfactory, and accoustico-lateralis placodes) first evolved at the base of the chordate lineage, while others might be specific to vertebrates. Combined with morphological and cellular fate data, these results also suggest that the sensory placodes of the ancestor of all chordates differentiated into a wide range of structures, most likely to fit the lifestyle and environment of each species.